Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Pengajar Melalui Mediasi Kompetensi - Asep Hendiawan (Politeknik Ilmu Pelayaran Semarang, 2020)
This Research aim to to test and analyse training influence to instructor interest in Politeknik Ilmu Pelayaran Semarang. To test and analyse influence motivate to instructor interest of Politeknik Ilmu Pelayaran Semarang. To test and analyse training influence to instructor performance in Politeknik Ilmu Pelayaran Semarang. To test and analyse influence motivate to instructor performance in Politeknik Ilmu Pelayaran Semarang. To test and analyse interest influence to instructor performance of Politeknik Ilmu Pelayaran Semarang. Population in this research is instructor of Politeknik Ilmu Pelayaran Semarang amounting to 106 people. Intake of sample use census technique that is all population made as sample so that the amount of sample counted 106 people. As for data obtained with kuesioner with data analysis use linear regression. Pursuant to research which have been done by hence can be obtained by the following conclusion of Training have an effect on to interest. Motivation have an effect on to interest. Training have an effect on to instructor performance. Motivation have an effect on to instructor performance. Interest have an effect on to instructor performance. Interest do not training influence mediation to instructor performance. Interest do not influence mediation motivate to instructor performance